Flexible polyurethane foams reinforced with graphene and boron nitride nanofillers. Issue 3 (8th December 2022) - Li, Owen; Tamrakar, Sandeep; Iyigundogdu, Zeynep; Mielewski, Debbie; Wyss, Kevin; Tour, James M.; Kiziltas, Alper
Abstract: The effect of three types of nanofillers on the physical, mechanical, and thermal properties of flexible polyurethane foams (FPUF) was studied. FPUF with nanofillers are of interest to the automotive industry due to their potential for enhancing compression properties and enabling sustainable foams. Holey and wrinkled flash graphene, and untreated and silane coated boron nitride were tested as fillers up to 0.1 wt% loading level. Flash graphene filled FPUF showed significant improvement in compressive properties, especially at the 0.025 wt% loading level, showing a 22% increase in compressive force deflection at 25% strain and a 17% increase at 50% strain compared to the unfilled control foam sample. Boron nitride nanoparticles, treated and untreated, were shown to be an effective means of reducing wet compression set properties, addressing a key area of concern for sustainable polyols. Wet compression set was reduced by 20%–30% for most boron nitride foams compared to their unfilled control samples. Boron nitride may enable implementation of more sustainable polyols in automotive FPUF. Nanofillers did not significantly improve thermal stability of FPUF. Abstract : Boron nitride decreases wet compression set. Graphene improves compression properties.